Limbal Stem Cell Deficiency: Current Treatment Options and Emerging Therapies - Michel Haagdorens; Sara Ilse Van Acker; Veerle Van Gerwen; Sorcha Ní Dhubhghaill; Carina Koppen; Marie-José Tassignon; Nadia Zakaria (Stem Cells International)
Severe ocular surface disease can result in limbal stem cell deficiency (LSCD), a condition leading to decreased visual acuity, photophobia, and ocular pain. To restore the ocular surface in advanced stem cell deficient corneas, an autologous or allogenic limbal stem cell transplantation is performed. In recent years, the risk of secondary LSCD due to removal of large limbal grafts has been significantly reduced by the optimization of cultivated limbal epithelial transplantation (CLET). Despite the great successes of CLET, there still is room for improvement as overall success rate is 70% and visual acuity often remains suboptimal after successful transplantation. Simple limbal epithelial transplantation reports higher success rates but has not been performed in as many patients yet. This review focuses on limbal epithelial stem cells and the pathophysiology of LSCD. State-of-the-art therapeutic management of LSCD is described, and new and evolving techniques in ocular surface regeneration are being discussed, in particular, advantages and disadvantages of alternative cell scaffolds and cell sources for cell based ocular surface reconstruction.